Answer:
348
Step-by-step explanation:
Hi there,
Take y from first equation and use it / substitute it into the second equation:
-2x + 8 = x - 1, so 3x = 9, therefore x = 3.
Then y = x - 1 = 3 - 1 => y = 2.
Solution is (3,2).
A quick check: 2 = -2*3 + 8, true, and 3 = 2 - 1, also true.
Green eyes.
Ni : Zn: Cu = 7:2:9 =7x : 2x : 9x
7x+2x+9x = 3.8
18x=3.8
x=3.8/18=1.9/9≈0.21
Ni: 7x=7*0.21=1.47 ≈1.5 kg
Zn: 2x=2*0.21=0.42≈0.4 kg
Cu: 9x=9*0.21=1.89 ≈1.9 kg
Check 1.5+0.4+1.9 =3.8 True
Answer:
I'm in eight grade so don't assume i'm right. But from looking at this. It looks like x-1=8 and y+1= 28. I'm only doing High School Math 1 in eight grade tho. So if i'm wrong i'm sorry
Step-by-step explanation: